ANALISIS INDIKATOR KEPEMIMPINAN TEKNOLOGI KEPALA SEKOLAH SEBAGAI PEMIMPIN IMPLEMENTASI TEKNOLOGI ABAD 21 - Dasmo, Dasmo; Notosudjono, Didik; Sunardi, Oding; Binoardi, Hikmah (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: Analysis of Principal Technology Leadership Indicators as Leaders of 21st Century Technology Implementation 21st century principals must be leaders in technology implementation by using technology as the primary tool for transforming teaching and learning. Through technological leadership, principals can utilize the talents and potential of teachers to produce superior pedagogical methods based on information and communication technology (ICT). This study aims to describe technological leadership and the indicators that mark the principal's technological leadership style as a leadership style that must be developed in the 21st century. The study was conducted using the literature study method, where information was obtained from journals, literature books, research reports, mass media, and written sources, both printed and electronic. Based on the results of the study obtained 7 indicators to measure the principal's technological leadership, namely: (1) vision, planning, and management; (2) interpersonal and communication skills; (3) teacher development and training; (4) technology and infrastructure support; (5) excellence in professional practice; (6) digital learning and teaching culture; (7) digital citizenship; and (8) evaluation and assessment. Strengthening the principal's technological leadership is expected to optimize the innovative behavior of teachers which can improve the quality of education. Abstrak: Analisis Indikator Kepemimpinan Teknologi Kepala Sekolah Sebagai Pemimpin Implementasi Teknologi Abad 21 Kepala sekolah abad 21 harus menjadi pemimpin implementasi teknologi dengan menggunakan teknologi sebagai alat utama untuk mengubah pengajaran dan pembelajaran. Melalui kepemimpinan teknologi, kepala sekolah dapat memanfaatkan bakat dan potensi guru untuk menghasilkan metode pedagogis yang unggul berbasis teknologi informasi dan komunikasi (TIK). Penelitian ini bertujuan untuk mendeskripsikan kepemimpinan teknologi dan indikator-indikator yang menandai gaya kepemimpinan teknologi kepala sekolah sebagai gaya kepemimpinan yang harus dikembangkan pada abad 21. Penelitian dilakukan menggunakan metode studi kepustakaan, dimana informasi diperoleh dari jurnal, buku literatur, laporan penelitian, media masa, dan sumber-sumber tertulis baik cetak maupun elektronik. Berdasarkan hasil penelitian diperoleh 7 indikator untuk mengukur kepemimpinan teknologi kepala sekolah yaitu: (1) visi, perencanaan, dan manajemen; (2) keterampilan interpersonal dan komunikasi; (3) pengembangan dan pelatihan guru; (4) dukungan teknologi dan infrastruktur; (5) keunggulan dalam praktik professional; (6) budaya belajar dan mengajar digital; (7) digital citizenship; dan (8) evaluasi dan penilaian. Penguatan kepemimpinan teknologi kepala sekolah diharapkan dapat mengoptimalkan perilaku inovatif guru yang dapat meningkatkan mutu pendidikan.